Peranan Kepolisian dalam Penanggulangan Premanisme di Wilayah Hukum Polda Bali - Anak Agung Putri Chandra Dwivasari; I Wayan Eka Artajaya (Jurnal Hukum Mahasiswa, 2026)
Thuggery remains a social ill that can disrupt public order and security, necessitating effective, measurable, and sustainable measures. This study aims to analyze the role of the Bali Regional Police and the obstacles faced in combating thuggery within its jurisdiction. This study uses a juridical-empirical method, combining literature studies, laws and regulations, and field data through interviews and observations. The results show that the Bali Regional Police have implemented various strategies, one of which is Operation Pekat Agung. This police operation is supported by strategies such as a preemptive approach by providing counseling regarding thuggery, a preventive approach through community development, and repressive law enforcement against perpetrators of thuggery. However, several obstacles remain, both in terms of structure, substance, and legal culture. This study concludes that the police's role has not been effective, but that strengthening coordination, improving human resources, and community participation are needed to create a safe and orderly environment in Bali on an ongoing basis